The Impact of Digital Parenting on the Social Behavior of Children Aged 7–12 Years - Tsang, Ghea; Wong, Wing Kei (Acta Psychologia, 2025)
This research explores the impact of digital parenting on the social behavior of children aged 7–12 years, a developmental stage marked by increasing independence and digital exposure. As technology becomes deeply integrated into children's daily lives, parental approaches to managing digital consumption through monitoring, communication, and engagement play a crucial role in shaping social outcomes. Using a mixed-methods approach, this study involved surveys and interviews with parents, teachers, and children to examine how different digital parenting styles affect children's empathy, cooperation, peer interaction, and emotional regulation. Findings indicate that children whose parents are actively involved in their digital lives by setting clear boundaries, encouraging open dialogue, and participating in online activities demonstrate better social adaptation, stronger emotional control, and healthier peer relationships. In contrast, excessive control without constructive communication is associated with rebellious tendencies and antisocial behaviors. The study offers valuable implications for parents, educators, and policymakers. It highlights the need for balanced digital parenting that combines guidance with trust, as well as the importance of collaborative efforts to support children's social development in digital contexts. Ultimately, the research contributes to the broader understanding of how digital environments interact with family dynamics to influence child behavior and development.